Counselling psychology in South Korea. Issue 2 (2nd April 2016) - Ju, Young A.; Han, Young-joo; Lee, Hyejin; Lee, Dong-gwi
Abstract : Counselling psychology (CP) in South Korea has grown tremendously as it establishes its unique niche in the mental health profession. Diverse practice under the roof of CP is a strength as well as a weakness. In this paper, we describe the characteristics of CP in South Korea in terms of history, credentialing, the service delivery system, organizations, training, distinctive features from other adjacent areas, core values, and the profession's unique challenges and future directions. Future tasks include the establishment of clear professional identity, achievement of a governmental licensure system, a nationwide accreditation system, development of Korean-specific ways of counselling, protocols for trauma, and increased accessibility.